Effect of Oral Sodium Bicarbonate Treatment on 24-Hour Ambulatory Blood Pressure Measurements in Patients With Chronic Kidney Disease and Metabolic Acidosis - Gaggl, Martina; Repitz, Alexandra; Riesenhuber, Sonja; Aigner, Christof; Sliber, Christopher; Fraunschiel, Melanie; Cejka, Daniel; Sunder-Plassmann, Gere (Frontiers in Medicine, 2021)
Background: Sodium bicarbonate supplementation is a mainstay in treatment of metabolic acidosis in patients with chronic kidney disease (CKD). Recent studies showed reduction of progression of CKD and reduced all-cause mortality. However, additional sodium loading could worsen arterial hypertension, a well-known contributor to progression of CKD. This patient-relevant and economically negative side effect is under-studied in prospective studies up until now. Objective: The aim of this study was to analyze the effect of sodium bicarbonate treatment on arterial blood pressure at baseline and after eight weeks. Methods: The SoBic study is an ongoing randomized controlled trial, in which patients with CKD receive either a high dose of oral sodium bicarbonate or a rescue treatment, if necessary. We used standardized office blood pressure and 24-hours ambulatory blood pressure monitoring (24h-ABPM). Regression models were adjusted for estimated glomerular filtration rate and change of antihypertensives. Results: 47 subjects were enrolled and the mean age was 57 (±14.6) years and 18 (38%) were female. In 43 randomized subjects with sufficiently performed 24h-ABPM neither systolic 24h-ABPM (2.522; 95%CI: -2.364, 7.408; mmHg) nor diastolic 24h-ABPM (0.868; 95%CI: -2.411, 4.147; mmHg) was affected by study group allocation. When looking at the effect of individual sodium bicarbonate dose on 24h-ABPM, the fully adjusted model suggested an increase of 0.047 (95%CI: -0.026, 0.119) mmHg by each mg/kg per day increase of sodium bicarbonate dose. Conclusion: Sodium bicarbonate supplementation over 8 weeks did not significantly increase blood pressure measured by 24h-ABPM in CKD patients.